What Is Perception?: Interpreting “Flesh, Chiasm (L'entrelacs-Le Chiasme) According To Maurice Merleau-Ponty - Paulus Eko Kristianto (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2023)
The study of the body and chiasm according to Merleau-Ponty is an interesting subject that deserves to be explored. This is because it touches the